Taxonomy of the water beetle genus Limnebius Leach in southern Africa (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2015)
The southern African species of the water beetle genus Limnebius Leach, 1815, are revised. Eleven new species are described, based on the examination and databasing of 6,201 specimens from 96 localities/events. Male genitalia are illustrated, and high resolution habitus images of the holotypes are provided. Distribution maps are provided for the eleven species now known from southern Africa, including Namibia, South Africa, Zambia, Zimbabwe, and the extreme southern part of Angola. New species of Limnebius are: L. capensis (South Africa: Western Cape Province, W. Cape, Hawequas); L. convexus (South Africa: Western Cape Province, Little Karroo, Raubenheimer Dam); L. endroedyi (Namibia: C. Namib desert, Numis Wasser); L. kavango (Namibia: Kavango: Mahango Game Reserve); L. masculinus (South Africa: KwaZulu-Natal Province, Hluhluwe Game Reserve); L. probus (South Africa: KwaZulu-Natal Province, Zululand, Dukuduku Forest Station); L. quantillus (South Africa: Limpopo Province, N. Transvaal, Mmabolela estate); L. retiolus (South Africa: Northern Cape Province, Cape Farm Ezelsfontein); L. speculus (South Africa: KwaZulu-Natal Province, Hluhluwe Game Reserve); L. suaviculus (South Africa: KwaZulu-Natal Province, Tugela River near Olivershoek road); L. transversus (South Africa: KwaZulu-Natal Province, Mtubatuba).